Analysis on IP-based density of Internet - XU Ye; ZHAO Hai; SU Wei-ji; ZHANG Wen-bo; ZHANG Xin; WANG Zu-wei (Tongxin xuebao)
Physical properties of Internet were discussed. Based on analysis of giant data, IP-based density, a physical property parameter of Internet spacial validity, was firstly formally defined. Then a fitting model of density was generated by GA. What’s more, the fitting model was evaluated in several ways such as quantitative and qualitative analysis, fitting and forecast correctness of the model. Condition of Internet in the future, especially in Aug. 2008 when Olympic Games will be held in Beijing, was forecasted by the model and a result was yielded that Internet in August 2008 will be highly available.